DISCOVERY OF RADIAL VELOCITY VARIABLE POST-AGB STARS FROM THE MUCHFUSS PROJECT - Reindl, N.; Geier, S.; Kupfer, Thomas; Schaffenroth, Veronika; Heber, Ulrich; Barlow, B. N.; Ostensen, R. H. (2015)
In the course of the MUCHFUSS project we have discovered five radial velocity (RV) post-AGB stars. Among them, we found the first known RV variable 0(He) star, the only second known RV variable PG 1159 close binary candidate and three RV variable, H-rich post-AGB stars of O(H)-type.